From Digital Discourse to Language Learning: Investigating Indonesian-English Code-Mixing on Instagram Among Indonesian Youth - Maharani, Prita Setya; Mahdi, Rian Jumadil; Azizah, Shelvi Fitria (UICELE, 2026)
Social media has become an integral part of communication among Indonesian youth, creating a digital environment where multiple languages are frequently used. One common phenomenon on Instagram is Indonesian-English code-mixing, which appears in posts and comment sections. While previous studies have mainly examined code-mixing from sociolinguistic and identity-related perspectives, its potential role in informal English language learning remains underexplored. This study investigates the types and functions of Indonesian-English code-mixing on Instagram and explores how such practices may facilitate English language exposure among Indonesian youth. Using a qualitative descriptive approach, data were collected from thirty Instagram posts and their corresponding comments from three youth-oriented media accounts: @herbyuss, @ussfeeds, and @volix.media. The data were analyzed using Muysken’s (2000) typology of code-mixing. The findings indicate that insertion is the most pervasive type, though congruent lexicalization also appears frequently, particularly through Indonesian affixes attached to English roots. Mixing density varies by account register: lifestyle and youth-oriented accounts display dense, playful code-mixing, while the news-oriented account restricts English use mainly to proper nouns and technical terms. These patterns suggest that informal accounts expose users to more structurally integrated English, offering opportunities for incidental exposure in authentic interactions that support natural language learning.